ANALISIS TITIK IMPAS DAN RESIKO PENDAPATAN USAHA TERNAK ITIK PETELUR DI DESA SUGIH WARAS KECAMATAN BELITANG MULYA KABUPATEN OGAN KOMERING ULU TIMUR - LASTINAWATI, ENDANG (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
This study aimed to analyze the break even point and the risk of laying ducks farm income in Sugih Waras Village, Belitang Mulya Subdistrict, Ogan Komering Ulu (OKU) Timur District. The research location is determined on purposive and make all laying duck farmers using cages 15 x 5 m and 15 x 6 m or raising ± 150 laying ducks in Sugih Waras Village as the respondents of this study (census methods). The results showed that laying ducks farmers in Sugih Waras Village reach the break even point at the time of production by 740 egg per month with a price is Rp 1.111.675,13 per egg. Laying ducks farm in Sugih Waras Village likely losses indicated by the variation coefficient of 1,026 and the lower limit revenue of -1.380.102,9.Keywords : break even point, the risk of income, laying ducks